"A reliable broadcast protocol" - Segall, Adrian; Awerbuch, Baruch (1982 21st IEEE Conference on Decision and Control, 1982)
Broadcast in a communication network is the delivery of copies of messages to all nodes. A broadcast algorithm is reliable if all messages reach all nodes in finite time, in the correct order and with no duplication. The present paper presents an efficient, reliable broadcast algorithm.